Evaluating the Environmental Impact of Anthropogenic Activities on Human Health: A Systematic Review - Luigi Cofone; Marise Sabato; Enrico Di Rosa; Chiara Colombo; Lorenzo Paglione (Urban Science, 2024)
Due to major global urbanisation, a careful evaluation of plans (town planning and mobility) and projects (industrial and development) is required in order to measure their impact on health and environmental matrices. In Italy, Legislative Decree No 152/06 introduced two procedures: the EIA (Environmental Impact Assessment) and SIA (Strategic Impact Assessment). Their focus, however, does not consider human health. Recently, the Integrated Environmental and Health Impact Assessment (IEHIA) was introduced; this defines the parameters necessary to provide an EIA that includes human health as a factor. This systematic review was conducted, including both the population impacted by new facilities and the method used to define their impact. Our database search produced 724 articles, of which 33 were eligible. Studies included landfill plans, manufacturing industries, mobility policies, energy production, and the environmental health of an area. All studies show how an approach encompassing multiple parameters can analyse the impact of a new facility in a comprehensive manner. This review shows that the use of health-related environmental impact parameters is essential for the integration of a project into a community, and can allow a wider understanding of the possible impacts on human health, both direct and indirect.